2009
DOI: 10.1016/j.mehy.2008.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the stalk effect: A new hypothesis explaining suprasellar tumor-induced hyperprolactinemia

Abstract: The pars tuberalis is a distinct subdivision of the pituitary gland but its function remains poorly understood. Suprasellar tumors in this pars tuberalis region are frequently accompanied by hyperprolactinemia. As these tumors do not immunoreact for any of the established pituitary hormones, they are classified as non-secretory. It has been postulated that these suprasellar tumors induce hyperprolactinemia by compressing the pituitary stalk, resulting in impaired dopamine delivery to the pituitary and, consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Earlier studies have reported Substance P and NKA in the ovine PT and had suggested that these peptides could act as PRL secretagogues [20, 21]. Previous studies in rodents showed that Substance P and NKA can act as potent regulators of pituitary hormone secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have reported Substance P and NKA in the ovine PT and had suggested that these peptides could act as PRL secretagogues [20, 21]. Previous studies in rodents showed that Substance P and NKA can act as potent regulators of pituitary hormone secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of MT1 melatonin receptors in the PT is known to inhibit adenylyl cyclase, and pharmacological studies in sheep have shown that melatonin impairs forskolin-induced hypersecretion of cAMP, with inhibition of prolactin from the PD through the reduction of a paracrine signal (44). However, although several compounds such as tachykinins, substance P, and neurokinin A are produced by the PT and can stimulate prolactin release (45)(46)(47), characterization of the chemical identity of that signal has been elusive. Here we show that the stimulatory effects of VEGF-A on prolactin were mimicked by conditioned media from PT cultures exposed to an NBS regimen of melatonin, and that these actions of PT media were blocked by a specific VEGF-A xxx a antibody, demonstrating that VEGF-A is a potential paracrine signal, and that melatonin-induced differential VEGF-A isoform production by the PT can regulate the seasonal production of prolactin and FSH.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactinomas are the most common (20% of cases of pituitary apoplexy); this is related to the frequency of prolactinoma in the population and to their frequent hemorrhagic nature. Hyperprolactin can also result from stalk effect [88].…”
Section: Endocrine Function 71 Pituitary Hormone Excessmentioning
confidence: 99%